The role of insulin-like growth factor-1 in the pathogenesis of cancer and inflammatory skin diseases - Marek-Safiejko, Magda; Myśliwiec, Hanna; Bączyk, Justyna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2020)
Insulin-like growth factor 1 belongs to the group of polypeptide growth factors. It plays a special role in the regulation of pre- and postnatal growth of the organism, and also has a hypoglycaemic, neuro-, and osteo- and chondroprotective effect. Numerous reports emphasize the role of insulin-like growth factor 1 in the pathogenesis of many cancers, such as breast cancer, prostate cancer, colorectal cancer and lung cancer. Its significant effect in the pathogenesis of some inflammatory skin diseases and in the development of skin cancers, e.g. basal cell carcinoma, squamous cell carcinoma or melanoma has been demonstrated. The article reviews the literature on insulin-like growth factor 1, its receptors and binding proteins, and the role in the pathogenesis of selected skin diseases.